2012
DOI: 10.1177/0164027512469214
|View full text |Cite
|
Sign up to set email alerts
|

Age-Friendly Environments and Self-Rated Health:

Abstract: While a number of organizations and government entities have encouraged the development of more "age-friendly" environments, to date there has been limited research linking these environment features to elder outcomes. Using a representative sample of older adults living in Detroit, this study examined the association between age-friendly environment factors and self-rated health. Results indicated that access to health care, social support, and community engagement were each associated with better self-rated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 68 publications
4
66
1
Order By: Relevance
“…Previous studies found that the following age-friendly environment factors may be associated with better quality of life, well-being, life satisfaction, or self-rated health among older adults: social environment such as social support from family, friends and neighbours [5,6,7,8], neighbourhood social cohesion [8,9,10,11,12,13], social trust [14,15], an aesthetic neighbourhood or pleasant physical environment [11,16,17,18], a walkable neighbourhood [19,20], neighbourhood service accessibility [5,21,22], perceived neighbourhood security and safety [23,24,25], and neighbourhood crime safety [26,27]. There is a lack of studies in Southeast Asia, including Thailand, investigating age-friendly environments and how these impact quality of life among older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found that the following age-friendly environment factors may be associated with better quality of life, well-being, life satisfaction, or self-rated health among older adults: social environment such as social support from family, friends and neighbours [5,6,7,8], neighbourhood social cohesion [8,9,10,11,12,13], social trust [14,15], an aesthetic neighbourhood or pleasant physical environment [11,16,17,18], a walkable neighbourhood [19,20], neighbourhood service accessibility [5,21,22], perceived neighbourhood security and safety [23,24,25], and neighbourhood crime safety [26,27]. There is a lack of studies in Southeast Asia, including Thailand, investigating age-friendly environments and how these impact quality of life among older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, members of the most vulnerable subgroup in the Korean context-poor older adults living alone-are more likely to have higher life satisfaction when they have higher levels of support in physical and social environments. As the first studies to examine the features of an age-friendly environment, these findings together suggest that more research is needed to examine replicability and applicability of the concept across diverse contexts and populations [12].…”
Section: Empirical Assessment Of the Structure Of Age-friendly Enviromentioning
confidence: 99%
“…Using these six environmental factors, Lehning and colleagues [12] studied the self-rated health of older adults as an indicator of well-being and found that environmental factors were significantly related to self-rated health above and beyond individual demographic and health characteristics. Specifically, access to health care, social support, and community engagement were associated with better self-rated health, while neighborhood problems were associated with poorer self-rated health.…”
Section: Empirical Assessment Of the Structure Of Age-friendly Enviromentioning
confidence: 99%
“…There were relatively few studies identified with three studies related to Active Living Communities [40][41][42]; one each for Safe communities [43] and Smart growth [44] and two related to Age Friendly Cities [45,46]. While various study designs were employed, none were randomized controlled trials.…”
Section: Safe Routes To Schoolmentioning
confidence: 99%
“…Despite this finding, there is a gap in knowledge about the holistic impact of Age-Friendly Initiatives on outcomes in the lives of older persons. The disparate results of the two studies suggest that further empirical evidence is needed that employs standardized definitions of age-friendly environments across diverse settings and health outcomes [45,46].…”
Section: Age-friendly Citiesmentioning
confidence: 99%